1994
DOI: 10.1007/bf02245326
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine modulates effects of stress on acoustic startle reflexes in rats: dependence on dose, stressor and initial reactivity

Abstract: Cigarette smokers report that one reason for smoking is that smoking helps them cope with stress, but there is conflicting evidence as to whether nicotine reduces physiological and behavioral responses to stress. The acoustic startle reflex amplitude, pre-pulse inhibition, and habituation of the reflex provide quantifiable measures of behavioral reactivity that may be sensitive to stress-induced changes that are altered by nicotine. In the present experiment, rats classified as high and low reactors according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 62 publications
6
72
4
Order By: Relevance
“…Animal studies have shown that nicotine enhances acoustic PPI in some rodent strains (Acri, 1994;Curzon et al, 1994;Acri et al, 1995;Faraday et al, 1999;Schreiber et al, 2002;Spielewoy and Markou, 2004); an effect thought to be mediated by nicotinic acetylcholine receptors (nAChRs) (Schreiber et al, 2002;Suemaru et al, 2004). However, other studies have shown no effect, or even the opposite effect (Decker et al, 1997;Faraday et al, 1999;Mirza et al, 2000;Schreiber et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that nicotine enhances acoustic PPI in some rodent strains (Acri, 1994;Curzon et al, 1994;Acri et al, 1995;Faraday et al, 1999;Schreiber et al, 2002;Spielewoy and Markou, 2004); an effect thought to be mediated by nicotinic acetylcholine receptors (nAChRs) (Schreiber et al, 2002;Suemaru et al, 2004). However, other studies have shown no effect, or even the opposite effect (Decker et al, 1997;Faraday et al, 1999;Mirza et al, 2000;Schreiber et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…2) The Acoustic Startle Reflex and Pre-Pulse Inhibition: Behavioral Indices of Attention Changes in attentional processes as a result of nicotine administration also have been reported in rats as measured by the acoustic startle reflex (ASR) and pre-pulse inhibition paradigm (Acri, Morse, & Grunberg, 1991;Acri, 1992;Helton, Modlin, Tizzano, & Rasmussen, 1993;Acri, Morse, Papke, & Grunberg, 1994;Acri, 1994;CUTZon, Kim, & Decker, 1994;Acri, Brown, Saah, & Grunberg, 1995;Rasmussen, Czachura, Kallman, & Helton, 1996). The ASR and prepulse inhibition of the ASR are behavioral responses believed to index central processes related to information processing (Swerdlow, Caine, Braff, & Geyer, 1992) and possibly attention CAcri et al, 1991;Acri, 1992Acri, , 1994Acri et al, 1994;Popke et aI., 1994;Acri et aI., 1995).…”
Section: ) Effects Of Nicotinementioning
confidence: 99%
“…Specifically, in empirical studies, nicotine administration decreased body weight in humans and rats (Grunberg, 1982;Winders & Grunberg, 1989), decreased aggression in humans (Cherek, 1981;Cherek et aI., 1991) and in rats (Silvennan, 1971;ScheufeJe, 1997), and altered biochemical and behavioral responses to stress in rats (Benwell & Balfour, 1982;Cam & Bassett, 1983;1984;Sharp, Beyer, Levine, Morley, & McAllen. 1987;Peck, Dilsaver, & McGee, 1991;Acri, 1992Acri, , 1994Takada, Thara, Vrano, & Takada, 1995) and in humans (MacDougall, Musante, Castillo, & Acevedo, 1988;Gilbert, Robinson, Chamberlin, & Spielberger, 1989;Pomerleau & Pomerleau, 1990;Levin, Rose, Behm, & Caskey, 1991;Smits, Temme, & Thien, 1993).…”
Section: ) Effects Of Nicotinementioning
confidence: 99%
See 2 more Smart Citations